PERUBAHAN PERAN MAMAK TERHADAP KAMANAKAN DALAM KELUARGA BATIH DI KANAGARIAN BAYUA KECAMATAN TANJUNG RAYA KABUPATEN AGAM SUMATERA BARAT - Yuni Ariska; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Mamak's role in kamanakan is to guide and teach customs to kamanakan. Mamak acts as a leader for his kamanakan and kamanakan is a person led by mamak. The role of a mamak in Minangkabau is very much needed for a boy who will grow up. Mamak will give more guidance, religious teaching for children both boy about morals and especially supervise the behavior of children kamanakan. The role of mamak is considered to be both important and heavy, as the saying "children on the lap will be supervised". If there are problems in the family, mamak is responsible for resolving the problem. The role of mamak today has changed like never before. This qualitative research uses the Purposive Sampling technique. The results of this study are to know the changes in the role of mamak in kamanakan, especially in guiding and teaching children kamanakan. As well as its role in terms of economics, education, determining began to decrease. However, to manage and maintain the inheritance of mamak still plays a role, but there are also mamak who do not play a role. Mamak is a place to ask for children kamanakan, so that you know how the role of mamak and the role as children kamanakan. The fact is that there is no mamak function on the run, when childish children violate customary norms, mamak only gives limited advice, so that children who commit wrongdoing do not appear ashamed by their actions. Keywords: Social Change, Mamak and the Influence of External Culture